Pelatihan Penanganan Trauma Pada Kegawatdaruratan Bagi Satuan Polisi Pamong Praja Kabupaten Tegal - Ikawati Setyaningrum; Deni Irawan; Dwi Budi Prastiani; Khodijah Khodijah (UNIVERSITAS BHAMADA SLAWI, 2020)
Anemia is a serious nutritional problem in Indonesia. According to Riskesdas in 2013, the prevalence of anemia in Indonesia was 21.7%, males 18.4% and women 23.9%. The proportion of anemia according to adolescence is at the age of 15-24 years which is 18.4%. Anemia can cause many negative effects on teenagers. Among them is a decrease in concentration of learning, stamina and work productivity. Iron absorption is not only influenced by nutrition but is also caused by the presence of substances that can inhibit the absorption of these nutrients. Other factors are lifestyle, socioeconomic, demographic, education, gender, age and region. Public health strategies to prevent and control anemia are very important to prevent future mortality and morbidity events. The aim of community service is to reduce the prevalence of anemia in adolescents through examinations, Fe tablets and counseling. The target activity is the students of An Nur Tegal Vocational School in Central Java Province with a total of 26 teenagers. Proactive teen activity results in examinations and counseling. The importance of detecting, examining risk factors that affect anemia in adolescents and counseling on prevention and treatment of anemia so that high-risk adolescents need to be considered for follow-up to controlling risk factors. Appropriate health education needs to be provided at home and school so that these risk factors can be eliminated at an early stage.